2016
DOI: 10.5500/wjt.v6.i4.675
|View full text |Cite
|
Sign up to set email alerts
|

Review of allogeneic hematopoietic stem cell transplantation with reduced intensity conditioning in solid tumors excluding breast cancer

Abstract: Solid tumors in adults constitute a heterogeneous group of malignancy originating from various organ systems. Solid tumors are not completely curable by chemotherapy, even though some subgroups are very chemo-sensitive. Recently, oncologists have focused on the use of allogeneic hematopoietic stem cell transplantation (allo-HSCT) with reduced intensity conditioning (RIC) for the treatment of some refractory solid tumors. After the demonstration of allogeneic graft-versus-leukemia effect in patients with hemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The method is a potentially curative therapeutic approach and is mostly used among patients with hematologic malignancies and myelodysplastic syndromes. It is also introduced in the solid tumors treatment schemes, as well as bone marrow failure syndromes, primary immunodeficiencies, and inborn errors of metabolism [2][3][4]. Depending on the treatment protocol, a patient can be a self-donor (autologous transplantation) or another unrelated person can be a donor for the patient (allogeneic transplantation) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method is a potentially curative therapeutic approach and is mostly used among patients with hematologic malignancies and myelodysplastic syndromes. It is also introduced in the solid tumors treatment schemes, as well as bone marrow failure syndromes, primary immunodeficiencies, and inborn errors of metabolism [2][3][4]. Depending on the treatment protocol, a patient can be a self-donor (autologous transplantation) or another unrelated person can be a donor for the patient (allogeneic transplantation) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…It is also introduced in the solid tumors treatment schemes, as well as bone marrow failure syndromes, primary immunodeficiencies, and inborn errors of metabolism [2][3][4]. Depending on the treatment protocol, a patient can be a self-donor (autologous transplantation) or another unrelated person can be a donor for the patient (allogeneic transplantation) [1][2][3]. The procedure involves hematopoietic stem cell collection from peripheral blood after mobilization of stem cells with granulocyte-colony-stimulating factor from bone marrow, bone marrow collection, or cord blood collection from the donor.…”
Section: Introductionmentioning
confidence: 99%
“…Allogeneic haematopoietic stem cell transplantation (HSCT) has been shown to lead to an antitumor effect, based on allogeneic graft-versus-leukemia induction, which recently resulted in the expansion of HSCT for the treatment of solid cancers. 158 Several single case studies with various success have been reported on stem cell transplantation in CCA. 159-162 In a recent study performed in 17 patients with CCA who received a combination of liver transplantation and HSCT, only 1 out of 17 patients had a long-term survival.…”
Section: Cholangiocarcinoma (Cca)mentioning
confidence: 99%